An Analysis Code Mixing Of “Go Visit Daddy In Canberra” By The Connell Twins Youtube Channel - Yantris, Rianty Dwi; Sembiring, Rony Arahta; Sihite, Jubilezer (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study discusses the phenomenon of code mixing in everyday communication, which is increasingly important in multilingual societies. Although there are many studies on code mixing, none have reviewed specifically on the YouTube channel